Machining of an involute worm gear drive using the surface definition procedure - Savas, Vedat; Ozay, Cetin; Yapici, Abdulkerim (Carl Hanser Verlag, 2015)
There is a need for special machines and methods for machining of an involute worm gear drive. Due to these necessities, the machines for involute profile machining are limited and the production costs are also excessive. There are general approaches applicable for various types of gearwheel machining. As known, involute worm gears are generally machined in two ways, namely by the rolling method and by form milling. The rolling method is the most widely used one. In this study, the aim is to develop a novel machining method for involute worm gear drive production, which can be more often used in industrial production. Furthermore, this method should reduce machining costs andsimplify the manufacturing process for involute gear drives. Thus, theoretical calculations for the involute form of worm gear drive have been done and an analytical model has been set up using Matlab M file. Machining coordinates of involute worm gear have been created and transformed to G codes. So, the involute curve has been formed. Accuracy of those derived machining codes has been tested by using a CNC Simulator program. Finally, an involute worm gear drive has been machined in a CNC lathe (with two axes) machine using grooving tool and the newly designed special tool holder.
Keywords: Involute worm gear drive; surface definition procedure; CNC